DOP45 Predicting late responders to filgotinib in patients with moderately to severely active Ulcerative Colitis: A post hoc analysis of SELECTION and SELECTIONLTE. (30th January 2023) - Matsuoka, K; Löwenberg, M; Fumery, M; Takatori, Y; Fujitani, Y; Oortwijn, A; Faes, M; Jamoul, C; Hibi, T
Abstract: Background: Filgotinib (FIL) is a once-daily, oral, Janus kinase 1 preferential inhibitor approved for the treatment of ulcerative colitis (UC) in Europe and Japan. Previous analyses of the SELECTION programme showed that, in patients with moderately to severely active UC, C-reactive protein, rectal bleeding and stool frequency at day 7 predicted response to FIL at week 10, 1 and that patients who did not respond to FIL induction benefited from an additional 12 weeks of FIL 200 mg. 2 This post hoc analysis was conducted to identify factors associated with late response to FIL. Methods: The SELECTION programme comprises a phase 2b/3, randomized, double-blind, placebo (PBO)-controlled study (SELECTION; NCT02914522) and its open-label, long-term extension (SELECTIONLTE; NCT02914535). Adult patients aged 18–75 years were randomized to FIL 100 mg, FIL 200 mg or PBO once daily for 11 weeks in the induction study. This post hoc analysis only included patients receiving FIL 200 mg who did not have clinical remission or a Mayo Clinic Score (MCS) response at week 10 of induction and who subsequently entered SELECTIONLTE on FIL 200 mg. Patient characteristics at induction baseline and changes in surrogate markers of response from baseline to week 4 of induction were compared between patients who had observed partial MCS (pMCS) response (pMCS late responders) or observed non-response (pMCS non-responders) at week 12 of SELECTIONLTE using univariate and multivariate logistic regression models. Results: In total, 160 patients were included (102 [63.8%] pMCS late responders and 58 [36.3%] pMCS non-responders) (Table 1). In univariate analysis, prior use of biologics was not significantly associated with late response to FIL. Changes in surrogate markers of response showed that none were significantly associated with late response (Figure 1). In multivariate analysis of baseline characteristics, older age was positively associated with late response to FIL (odds ratio [OR]: 1.042, 95% confidence interval [CI]: 1.011–1.073, p = 0.007), while body mass index (BMI) < 18.5 kg/m 2 (OR: 0.041, 95% CI: 0.003–0.519, p = 0.014) was negatively associated with late response. Conclusion: In SELECTION programme participants, older age was positively associated with late response to FIL 200 mg and BMI < 18.5 kg/m 2 was negatively associated with late response. These factors should be taken into account when monitoring patients on FIL with insufficient response at week 10. No other strong predictors were identified. The results of this analysis should be interpreted in the context of previous findings. 1 1. Feagan B et al. United European Gastroenterol J 2022;10(S8):462–3 2. Vermeire S et al. United European Gastroenterol J 2021;9(S8):215–6